(untitled) (Journal of Hama University, 2019)
This research examines ambiguity in Adonis’s poetry as one of the most essential, striking features of his poetry in particular, and of modern poetry in general. This ambiguity has given Adonis’s poetry a quality of semantic loss and a frame of vagueness that make it sometimes close to mystery, which makes the recipient feel perplexed in his attempt to search for meaning. This study attempts to help the reader take in Adonis’s poetry, without getting lost in the maze of his poetic text, and to enable him to get through to its wider world. And to do that, the concept of ‘ambiguity’ in general will be explained, and an overview of some old and modern critical views of ‘ambiguity’ ‘obscurity’ is given, in addition to giving illustrations of representations of this ambiguity, which is manifest in particular in a semantic loss caused by thematic absence, abstraction, the special use of a special poetic language, the use of Sufic gnostic language, and the use of symbolism and myth. After that, the study will point out some of the positive and negative effects of Adonis’s poetry.